Implications of phytolith and diatom assemblages in the cultural layers of prehistoric archaeological sites of Ban Non Wat and Nong Hua Raet in Northeast Thailand - Kanthilatha, Nelum; Boyd, William; Parr, Jeffery; Chang, Nigel (Taylor & Francis Group, 2017)
attached
Keywords: Phytolith and diatom, Hard floor formation, Rice processing, Northeast Thailand